(untitled) (Journal of Geography and Environmental Management, 2019)
In the conditions of arid climate the ecological-geomorphological consequences of the concentrated extraction of mineral raw materials have certain specificity. The deflation of mineral weight of mine dump and walls of operational borrow pits generate a large-scale intoxication of air basin. At the same time in and near mountain allotment the water erosion processes of unprotected soils, suffusion, land subsidence and processes of underflooding by mine waters are activated. The anthropogenic impact spreads and on the urbanized territories, including Karaganda city. The geomorphological optimization of nature management in arid landscapes and in the Central Kazakhstan is necessary in order to avoid the negative ecological consequences.